Problems of Disputes/Conflicts over Land Acquisition towards Development for Public Interest in Indonesia - Wahanisa, Rofi; Hidayat, Arif; Riyanto, R. Benny; Anggono, Bayu Dwi (International Journal of Criminology and Sociology, 2021)
The issue that will be discussed in this paper are problems causing disputes/conflicts over land acquisition toward development for the public interest. To address those problems, document and literature search as well as literature review are employed, including the cases of land acquisition that have occurred to be analyzed descriptively to achieve resolution to the problems. The results showed that land acquisition is closely related to eviction, land purchase, compensation, repressive actions of the apparatus, public reluctance to move from the acquired land, and public refusal towards the form and amount of the compensation. The problems due to land acquisition that provokes disputes/conflicts arise from three sources: a substance (in terms of regulations, or biased meaning of public interest), structure (the roles of officials/institutions related to land acquisition), and public. Regarding the fact that the existence of disputes/conflicts over land acquisition is frequently related to the issue of justice and public welfare, therefore, attention and efforts are practically needed to achieve justice and welfare, especially for those whose lands are acquired without ignoring the aspect of legal certainty as a characteristic of state law.